Concepção de um sistema de propulsão elétrica para um trator de 9 KW adequado para agricultura familiar - Melo, Rodnei Regis de (2019)
Inserted in a new concept of agricultural motorization, this thesis deals with the proposition and analysis of the performance of an electric propulsion system with the embedded drive system for a small electric tractor. A propulsion system was designed with a nominal power of 9 kW and implemented in a prototype electric tractor built on a real scale, based on the evaluation of living conditions and working environment of family agriculture in Brazil. Its structure is formed by an Electronic Command Unit (ECU), two inverters and two three-phase induction motors. An algorithm was applied to promote control functionalities aiming at greater use flexibility and performance improvement with the proposed system. A supervisory framework was also proposed for data storage and performance analysis. In order to investigate the proper performance of the electric propulsion system with the electric tractor embedded drive system, practical traction tests were carried out in different scenarios and configurations, where the methodology used was based on the CODE 2 document - OECD standard code for official performance testing of tractors (OECD, 2017). With the tensile tests performed, in which an average tensile force between 2602.46 N and 2870.22 N, and an average drawbar power between 4026 W and 4204.87 W were achieved, it was proved that the electric tractor offers full traction capacity, compatible for the development of family farming activities, without compromising its electromechanical structure. Also, with the data obtained from the field tests, it was found that to perform the same work the electric tractor showed a considerable improvement in terms of stability and energy consumption when adopting the implemented slip control. The energy consumed in the tests without active slip control ranged from 29.5 Wh to 32 Wh. For the tests with active slip control, the energy consumed ranged from 17.1 Wh to 18.55 Wh. That is, there were 42% energy savings with the implementation of the proposed control. Thus, the experimental results proved the evidence that the proposed system is technically viable in terms of driving versatility and performance in traction efficiency and energy consumption.